Risks of cataract surgery in solid and hematologic cancer survivors - Hyunjean Jung; Sunyeup Kim; Byoung Hyuck Kim; Christopher Seungkyu Lee; Suk Ho Byeon; Sung Soo Kim; Seung Won Lee; Yong Joon Kim (Scientific Reports)
Abstract In this nationwide retrospective cohort study, we investigated the risk of cataract surgery among cancer survivors compared to propensity score (PS)-matched non-cancer controls. This study included 4.5 million adults in the National Health Insurance Service database who underwent health screenings between year 2011 and 2014. PS-matching at a 3:1 ratio resulted in 167,766 non-cancer controls and 55,968 patients with cancer. During a period of up to 10 years, 7703 (13.8%) patients with cancer and 24,369 (14.5%) patients in the control group underwent cataract surgery. Survival analysis showed no difference in cataract surgery risk between the overall cancer cohort and controls. Analysis by cancer types showed that solid cancers did not increase the risk of cataract surgery compared to controls, whereas hematologic cancer survivors exhibited a significantly increased risk of cataract surgery, particularly between 2 and 5 years post-index date (hazard ratio at second year, 1.81; 95% confidence interval, 1.07–3.05; p = 0.027). Among hematologic cancer survivors, factors significantly associated with increased cataract surgery risk included advanced age, leukemia diagnosis, bone marrow transplantation, and prolonged steroid use. This study highlights the elevated risk of cataract surgery among hematologic cancer survivors, emphasizing the need for long-term ophthalmologic follow-up in this population.